Characteristics of Shale Pores and Surfaces and Their Potential Effects on the Fluid Flow From Shale Formation to Fractures - Li, Xu; Cai, Jingong; Gao, Bo; Long, Shengxiang; Feng, Dongjun; Peng, Zeyang; Guo, Benqiang (Frontiers in Earth Science, 2021)
Fluid flow is critical for the efficient exploitation of shale resources and can be split into two stages: the flow in the artificial fractures and, more importantly, the flow from shale formations to the artificial fractures. In this study, X-ray diffraction, N2 adsorption, mercury intrusion, and ethylene glycol monoethyl ether adsorption were conducted on the shales collected from Es3middle, Es3lower, and Es4upper sub-members in the Dongying Sag to reveal the potential effects of the characteristics and properties of pores and surfaces on the fluid flow in shale formations. The results are indicated as follows: 1) The shales from Es3middle and Es3lower contain more I/S and detrital minerals but less illite and carbonate minerals than those of Es4upper. 2) The shales from Es3middle and Es3lower are mainly composed of smaller pores present in larger surface areas and lead to the steeper slope between the BrunauerEmmettTeller specific surface area (BET-SSA) and pore volumes. 3) Clay minerals mainly contribute to pore development, and carbonate minerals inhibit pore development. All kinds of surface areas (especially the inner surface area) are sourced by clay minerals, while I/S and illite present opposite effects. 4) Pore size and surface properties affect significantly the fluid flow in shale formations. The shales from Es4upper are the favorable interval for shale oil accumulation and flow, especially for the shales with depth ranges of 3360∼3410 m, which possess high carbonates, illite and total organic carbon content, low clay mineral content, large pore volume, high large pore content, and small surface areas. Additionally, fluid composition needs to be paid more concern in the future.